Realistic Motion Avatars are the Future for Social Interaction in Virtual Reality - Rogers, Shane L.; Broadbent, Rebecca; Brown, Jemma; Fraser, Alan; Speelman, Craig P. (Frontiers in Virtual Reality, 2022)
This study evaluated participant self-reported appraisal of social interactions with another person in virtual reality (VR) where their conversational partner was represented by a realistic motion avatar. We use the term realistic motion avatar because: 1. The avatar was modelled to look like the conversational partner it represented, and 2. Full face and body motion capture was utilised so that the avatar mimicked the facial and body language of the conversational partner in real-time. We compared social interaction in VR with face-to-face interaction across two communicative contexts: 1. Getting acquainted conversation, and 2. A structured interview where the participant engaged in self-disclosure about positive and negative experiences. Overall, participants largely indicated they preferred face-to-face over VR communication. However, some participants did indicate a preference for VR communication. Additionally, an analysis of post-conversation ratings indicated no significant difference for rated enjoyment, understanding, self-disclosure, comfort, and awkwardness between communication modes. The only ratings where face-to-face was found to be superior was for perceived closeness across both types of communication, and for feeling understood specifically when disclosing negative experiences. Most participants perceived frequent eye contact in both face-to-face and VR interaction, but typically more eye contact when face-to-face. Eye contact was positively associated with rated enjoyment, closeness, feeling understood, and comfort. Overall, our findings suggest that harnessing full face and body motion capture can make social interaction in VR very similar to face-to-face interaction. We anticipate that VR social interaction is poised to become the next major technological evolution for human computer mediated communication and suggest avenues for further research.